2011
DOI: 10.1002/ejlt.201000500
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of green seed canola oil for in situ epoxidation

Abstract: Green seed canola oil is underutilized for edible purposes due to its high chlorophyll content, which makes it more susceptible to photo-oxidation and ultimately reduces the oxidation stability. The present work is an attempt to compare the kinetics of epoxidation of crude green seed canola oil (CGSCO) and treated green seed canola oil (TGSCO) with peroxyacids generated in situ in presence of an Amberlite IR-120 acidic ion exchange resin (AIER) as catalyst. Among the two oxygen carrier studied, acetic acid was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…For the reaction time range from 5 to 12 h an increase of the hydrogen peroxide-to-oil unsaturation mole ratio in the applied range from 1.1 to 1.5 increases the value of the relative epoxy yield ( Figure 6a). This is in agreement with findings in several published investigations of the process conditions influence on the epoxidation of different vegetable oils in which the "one-variable-at-a-time" method was applied [11,12,14,18].…”
Section: Influence Of the Process Conditions On The Relative Epoxy Yieldsupporting
confidence: 92%
See 2 more Smart Citations
“…For the reaction time range from 5 to 12 h an increase of the hydrogen peroxide-to-oil unsaturation mole ratio in the applied range from 1.1 to 1.5 increases the value of the relative epoxy yield ( Figure 6a). This is in agreement with findings in several published investigations of the process conditions influence on the epoxidation of different vegetable oils in which the "one-variable-at-a-time" method was applied [11,12,14,18].…”
Section: Influence Of the Process Conditions On The Relative Epoxy Yieldsupporting
confidence: 92%
“…Several studies confirmed that the maximal epoxy yield increases with an increase in excess of hydrogen peroxide up to 50%. Above the excess of 50%, the obtained results differed among the studies: in some of them the maximal epoxy yield decreased [14,28], whereas in the others it stayed almost constant [11,12] or even increased [18]. Hydrogen peroxide is applied as an aqueous solution, therefore higher amounts of hydrogen peroxide increases the volume of the waste water generated after the epoxidation process.…”
Section: Preliminary Experiments and Ranges Of The Process Conditionsmentioning
confidence: 93%
See 1 more Smart Citation
“…Investigations of such oils have largely been based on their availability and their degree of unsaturation. 10 Some common oils of interest are epoxidized soybean oil (ESO), 5,10−15 epoxidized canola oil (ECO), 16,17 and epoxidized linseed oil (ELO). 6,7,18−20 Each of these resins have shown different capacities for achieving fully formed networks; as expected, however, not all epoxidized oils are in fact equal.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Some studies analyzed 2–3 factors at a time but not the effects of all the main factors simultaneously. The design matrix of these studies were not well-defined and the number of treatments were not adequate for a robust model. Other studies analyzed four of the main factors simultaneously with a well-defined experimental design, but the studies either did not include the effect of varying catalyst amounts or the reaction time. , All of the main factors including stirring speed were studied by Mungroo et al, but the independent effect of the acetic acid and H 2 O 2 were not studied, and no model was proposed. In all of these optimization studies above, the reaction temperature was cooled manually or controlled by H 2 O 2 addition, which likely added variability within the experimental runs.…”
Section: Introductionmentioning
confidence: 99%